2021
DOI: 10.1001/jamanetworkopen.2021.8799
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Income Inequality and County-Level COVID-19 Cases and Deaths in the US

Abstract: Key Points Question How does the association between county-level income inequality, measured by the Gini coefficient, and COVID-19 cases and deaths change over time? Findings This ecological cohort study found that there was a positive correlation between Gini coefficients and county-level COVID-19 cases and deaths during the study period. The association between income inequality and COVID-19 cases and deaths varied over time and was strongest in the summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(116 citation statements)
references
References 18 publications
5
101
1
1
Order By: Relevance
“…These numbers were very high for NA and Europe continents which included states with population owning greater income [25,26]. As was written above, in some countries was found the association between GDP and COVID-19 death rates [28,30,33]. These investigations agree with presented in diagrams correlation ratio: significantly more COVID-patients have died in Europe and NA than in Asia or Africa (Fig.…”
Section: Quantitate Evaluation Of Socioeconomic Factors and Progress Of Virus Infectionsupporting
confidence: 75%
See 1 more Smart Citation
“…These numbers were very high for NA and Europe continents which included states with population owning greater income [25,26]. As was written above, in some countries was found the association between GDP and COVID-19 death rates [28,30,33]. These investigations agree with presented in diagrams correlation ratio: significantly more COVID-patients have died in Europe and NA than in Asia or Africa (Fig.…”
Section: Quantitate Evaluation Of Socioeconomic Factors and Progress Of Virus Infectionsupporting
confidence: 75%
“…Different categories of risks prompting of SARS-CoV-2 infection process or aggravating the course of the disease were generally analyzed by WHO and others experts [7,9,24,[27][28][29][30][31][32][33][34]. In the Tan and coworkers publication [33] was suggested that income disproportion in the USA associated with more infection cases and COVID-19 deaths. Recently was unpredictably found high mortality rates for well situated COVID-19 patients [9,30].…”
Section: Quantitate Evaluation Of Socioeconomic Factors and Progress Of Virus Infectionmentioning
confidence: 99%
“…Decisions about the course of each epidemic are based on an analysis of statistics on circulating infection in the population over the time period described. Epidemiologists, infectious disease specialists, clinicians and other experts analyze primarily the risks of an epidemic (pandemic) and their factors [5,[8][9][10][11][12][13][14][15][16][17][27][28][29]. The following available sources differentiate or assess risk factors for severity or mortality from COVID-19 [5,7].…”
Section: Risk Factors For the Epidemic Process Covid-19mentioning
confidence: 99%
“…The COVID-19 pandemic is a global health, medical, social and economic challenge now and as well as in the future. Many diverse factors increasing the onset and course of COVID-19 disease have been evaluated and analyzed [5,[7][8][9][10][11][12][13][14][15][16][17]. This review analyzes the influence of dietary factors on the development of the SARS-CoV-2 epidemic process on five continents and in some of their regions in order to assess the effectiveness of factors that can reduce the consequences of a severe infectious disease.…”
Section: Introductionmentioning
confidence: 99%
“…Communities required to live under curfew and heavy isolation requirements may have experienced additional strain. There are also equally alarming disparities in impact among racially and culturally defined groups ( Gorges and Konetzka, 2021 , Gu et al, 2020 , Knights et al, 2021 , Morlock et al, 2021 , Tan et al, 2021 ) and there exists a need to tailor public health messages accordingly ( Torres et al, 2021 ).…”
mentioning
confidence: 99%